Bitcoin Cycle through Markov Regime-Switching Model - Yi-Chun Shih; Wen-Tsung Huang; Pao-Peng Hsu (Engineering Proceedings)
We analyzed Bitcoin’s cyclical patterns used by the Markov regime-switching model and explored the impacts of inflation and the US Dollar Index on Bitcoin’s cyclicality. The results showed Bitcoin’s cyclical pattern, the effects of the US dollar index and VIX on Bitcoin’s cyclical pattern, and how the US dollar index and VIX affect BTC’s structural changes in Bitcoin.